PENGENDALIAN BIAYA UNTUK PENGHEMATAN BIAYA PRODUKSI PUDDING DENGAN METODE VARIABEL COSTING DI PT NIRAMAS UTAMA (INACO) - Soleman; Vivi Lusia; Mawan Arifin; Meilan Agustin (Universitas Borobudur, 2023)
The production costs at PT Niramas Utama (Inaco) are focused on the production costs of pudding, which include raw material costs, direct labor costs, and factory overhead costs. The increasing difference between the planned production costs and the actual costs indicates poor control over pudding production costs. To determine the magnitude of the difference and suitable methods for controlling production costs, this research is needed. The calculation of the Cost of Goods Manufactured for Pudding in 2017 is as follows: mango pudding: H2 - H1 = Rp. 5,000 - 2,512 = Rp. 2,488, passion fruit pudding: Rp. 5,000 - 2,422 = Rp. 2,578, and melon pudding: Rp. 4,800 - 2,849 = Rp. 1,951. The calculation of the Cost of Goods Manufactured for Pudding in 2019 is as follows: mango pudding: E H2 - H1 = Rp. 5,000 - 2,488 = Rp. 2,512, passion fruit pudding: Rp. 5,000 - 2,429 = Rp. 2,571. The company can achieve cost savings in the production of mango pudding amounting to Rp. 2,488, passion fruit pudding amounting to Rp. 2,578, and melon pudding amounting to Rp. 2,720. The results obtained from this research indicate that the variable costing method is capable of reducing costs for the cost of goods manufactured for pudding.